Вагон: роман / В. Н. Ажаев ;[ редактор Г. Калашников; художник Н. Стасевич] - Ажаев Василий Николаевич (Современник, 1988)
Экземпляры: Селтинская районная библиотека (аб) (20210220) / Инвентарный номер: 166586 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 34 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6